NCAA concussion education in ice hockey: an ineffective mandate - Kroshus, E.; Daneshvar, D. H.; Baugh, C. M.; Nowinski, C. J.; Cantu, R. C. (British Journal of Sports Medicine, 2014)
Background/aim: Despite concussion education being increasingly mandated by states and sports leagues, there has been limited evaluation of what education is in fact effective. The National Collegiate Athletic Association (NCAA) currently mandates that institutions provide concussion education, without specifying content or delivery. The present study evaluated the effectiveness of this general mandate, as enacted for male collegiate ice hockey teams within one conference of competition. Methods: In a prospective cohort design, 146 players from 6 male collegiate ice hockey teams in one Division 1 conference completed written surveys before and after receiving their institution-determined concussion education. Knowledge, attitudes, perceived norms and behavioural intention were assessed using validated measures. Education content and delivery was assessed by open-ended responses and consultation with team athletic trainers. Results: All teams received concussion education material; however, content and delivery varied. Rates of material recall differed by delivery format. Considering all teams together, there were no significant improvements in knowledge and only a very small decrease in intention to continue playing while experiencing symptoms of a concussion. Pre-education and post-education, there were significant between-team differences in attitudes towards concussion reporting and behavioural intention. Conclusions: The NCAA's general education mandate was divergently enacted; it did not significantly change the constructs of interest nor did it mitigate the pre-education team differences in these constructs. Existing educational materials should be evaluated, theory and evidence-driven materials developed, and mandates extended to, at a minimum, recommend materials found to be effective in changing concussion-reporting behaviour.